Industrial training report: Alfa Apparel Sdn Bhd (Telekung Rawdah) - Hamzah, Nurul Atiqah (Faculty of Business and Management, 2023)
This internship report presents an overview of the key experiences, learnings, and contributions during my internship at Alfa Apparel Sdn. Bhd (Telekung Rawdah). The internship spanned almost 6 months, and the primary objective was to gain practical industry exposure and apply academic knowledge in a real-world setting. Alfa Apparel Sdn. Bhd was established in February 2021 and released a product which is telekung or women's prayer wear and the product brand is known as Telekung Rawdah. Telekung Rawdah runs an online enterprise specializing in the manufacture and sale of premium quality telekungl women’s prayer wear. The Telekung Rawdah headquarter office is located at Putra Heights, Subang Jaya, where I have been placed to do an internship at the headquarters office. Telekung Rawdah also has an outlet located at Melawati Mall Kuala Lumpur. Telekung Rawdah strives to be one of the leading and best telekung manufacturers in Malaysia and globally. During the internship at Alfa Apparel Sdn. Bhd., I have been placed in the Department of Human Resources. The main task given to me as an intern here is the recruitment and selection of candidates. The internship objectives are to expose students to face the real - world of working. Students will get experience in development goals, skills enhancement, and gaining insights into the company's operations. At Alfa Apparel Sdn. Bhd., I learned about the standard operating procedures (SOPs) which are different for each employee according to their position and department. The tasks and responsibilities given to me include recruitment and selection of candidates, monitoring disciplinary actions among staff in the company, solving internal and external resources problems, and maintaining employees’ records. During the internship, I gained specific knowledge of how the industry operates and exposure to new technologies and methodologies. Besides, if any challenges are encountered during the internship, students need to take it positively and learn from their mistakes. During the internship, it is important to have interactions with the supervisor, colleagues, and other team members to enhance effective communication and collaboration in achieving objectives. During the internship period, demonstrated the practical application of academic knowledge and the contribution made to the success of Alfa Apparel Sdn. Bhd. to grow better in the future. The internship gives an impact to the student’s professional development and future career aspirations. It serves as a testament to the intern's growth and readiness to embark on a successful career in the chosen field.